Mixed Reality in Multiuser Participatory Design: Case Study of the Design of the 2022 Nordic Pavilion Exhibition at the Venice Biennale - Kai Reaver (Buildings, 2022)
The case study documents the design process of the physical and digital versions of the heritage-valued Nordic pavilion at the Venice Biennale. The case facilitated a multiuser collaboration in mixed reality (MR), studying the technologies’ influence upon user interactions and design decision making. Retitled as the ‘Sami Pavilion’ in tribute to the Sami artists from Norway, Sweden, and Finland, which the exhibition featured, the case study took place between 2019 and 2022, primarily during the COVID-19 pandemic. The context of the case study prompted a need to explore MR methods to overcome travel restrictions. While MR has shown some interesting utility in design research, the literature indicates the need for more concrete case work. It also was necessary to design a custom solution for multiuser collaboration. As the transferability of predictive design decisions in MR to the physical building relied upon replication between user experiences, the case embodied interesting challenges to prevalent Nordic architectural theory, particularly that of ‘genius loci’ or the ‘spirit of place’, which was a strong component of the heritage value of the building and, thus, an important design narrative. The case study documents how artworks and positions of artworks were tested in various configurations within the MR model by curators and designers to simulate the spatial experience of the design options. Several key design decisions were made based on the unique vantage points offered in MR. The MR model was then used to generate 2D technical documentation and installation instructions, which were installed on site. Studies to check the relationship between the MR model and the finished, physical result were conducted. Findings depicted a high degree of transferability between the MR model and the physical exhibition while noting discrepancies between the field of view (FOV) in the MR and physical spaces in which objects felt smaller in the real-life, built result. Possibilities and limitations for future MR ...